2008
DOI: 10.1177/1753425907087588
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a novel lipid A obtained from the lipopolysaccharide of Caulobacter crescentus

Abstract: Caulobacter crescentus CB15 is a dimorphic bacterium that is best known as a prokaryotic model for cell development. However, it is also being exploited in biotechnology, where the crystalline surface (S-layer) protein secretion system has been adapted for heterologous protein display or secretion. Because the S-layer attaches to the cell surface via lipopolysaccharide (LPS) and since the LPS represents a potential endotoxin contaminant of recombinant proteins, the lipid A component was examined in detail. LPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 35 publications
5
50
0
Order By: Relevance
“…earlier in Mesorhizobium huakuii (20) and Mesorhizobium loti strains (43), which contained a non-reducing trisaccharide backbone comprising a ␤-(136)-D-GlcpN3N disaccharide partly substituted with phosphate at C-4Ј and an ␣-(131)-linked D-GalpA in stoichiometric amounts. Other microorganisms that produce lipid A substituted with ␣-(131)-D-GalpA include A. pyrophilus (48), the stalk-forming bacterium Caulobacter crescentus (51), and the plant-growth promoting bacterium Azospirillum lipoferum (52). In the last case, the lipid A backbone constituted a GlcpN-disaccharide.…”
Section: Discussionmentioning
confidence: 99%
“…earlier in Mesorhizobium huakuii (20) and Mesorhizobium loti strains (43), which contained a non-reducing trisaccharide backbone comprising a ␤-(136)-D-GlcpN3N disaccharide partly substituted with phosphate at C-4Ј and an ␣-(131)-linked D-GalpA in stoichiometric amounts. Other microorganisms that produce lipid A substituted with ␣-(131)-D-GalpA include A. pyrophilus (48), the stalk-forming bacterium Caulobacter crescentus (51), and the plant-growth promoting bacterium Azospirillum lipoferum (52). In the last case, the lipid A backbone constituted a GlcpN-disaccharide.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the lipid A from mutant EL206 (rgtD Ϫ ) demonstrated the absence of GalA from the 4Ј-position and, therefore, showed that rgtD encodes the GalAT that transfers GalA to this position of the lipid A. Bacteria that contain 4Ј-galacturonosylated lipid A include R. leguminosarum and R. etli strains, which are members of the Rhizobiales (1), the stalk forming Caulobacter crescentus (34), and the hyperthermophile Aquifex aeolicus (35). Indeed, strains C. crescentus CB15 and A. aeolicus VF5 contain RgtD homologues (supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It can be cultivated readily to high densities on defined growth media consisting only of glucose and essential inorganic ions. Although a gram negative organism, its unusual lipopolysaccharide structure appears to have a much reduced sepsis potential, relative to enteric bacteria [9]. With these characteristics we expect the possibility that engineered strains can be formulated to be applied as stabilized killed organisms, designed to be applied to vaginal or other mucosal tissues at relevant times, such prior to sexual acts or childbirth, roughly comparable to spermicide use.…”
Section: Introductionmentioning
confidence: 99%